(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The present article elucidates the issues of thematic classification of phraseological units. In comparative-contrastive study of phraseological units the groups of thematic classification have been formed. The forming of phraseological units with “Clothing” component according to the themes in English, Russian and Uzbek languages have been discussed.